Etiological evaluation of amenorrhea: a cross-sectional study from a tertiary care center in India - Priya, Pritti K.; Aggarwal, Rohina; Chaudhary, Sumesh; Shah, Kunur; Solanki, Smit; Patel, Hetvi; Chhetry, Manisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: To determine the prevalence of etiological causes in cases with primary and secondary amenorrhea in a tertiary care center in Western India. Methods: A retrospective analysis of 170 medical records of non-pregnant women who presented with either primary or secondary amenorrhea to the Department of Obstetrics and Gynecology, IKDRC-ITS, Ahmedabad, Gujarat from Jan 2014 to December 2022 was done. The clinical profile, presentation, development of secondary sexual characteristics, physical examinations, hormone profile, imaging and cytogenetic study including karyotyping was done. Results: The most common causes of primary amenorrhea identified were end organ failure (71.49%), among these 69.41% had some form of Mullerian anomalies while three were cases of complete androgen insensitivity syndrome. This was followed by hormonal abnormalities (15.97%) and gonadal failure (7.63%). There were two cases of gonadal dysgenesis, three cases of Turner’s syndrome, three cases of complete androgen insensitivity, one case of Swyers syndrome, two cases of ring X chromosomes. Hypergonadotropic hypogonadism was the most common cause of secondary amenorrhea. Three patients had premature ovarian failure. Single kidney was the most common association seen in eleven patients. Conclusions: This is one of the large studies exploring causes of both primary and secondary amenorrhea in Western India. Mullerian anomaly was the commonest cause of primary amenorrhea followed by hormonal abnormalities and gonadal failure. Hypergonadotropic hypogonadism was the most common cause of secondary amenorrhea. Role of racial, genetic, epigenetic and environmental factors could be an area of future research.